Aerodynamic loads on porous fabrics and meshes - Scarabino, Ana Elena (2008)
This work presents drag coefficients of woven and knitted fabrics of extended use in facade protections, windbreak fences, hail shelters, etc. Wind loads are measured and analyzed for a square and a 4:1 rectangular frame respectively, covered with fabrics of optical porosity between 12 % and 75 %, for different angles of incidence of the wind. In one case, wind drag on a wet sample is compared with that on a dry sample. Results are compared with loads on an impermeable canvas, in order to obtain load reduction factors as functions of geometry and porosity. Loss coefficients k, when the flow is confined and forced through the fabric samples, are measured and reported for the different analyzed materials and related to the measured drag coefficients. Results are compared, when possible, with those of other researchers and with different semiempirical models.